2014
DOI: 10.2139/ssrn.2454257
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors Affecting Women's Susceptibility to HIV in India

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…This study was in accordance with a study done by Xu et al (2017), which stated that patients who want to know the status of HIV would be able to live their lives if they have family support and there was no discrimination. The prevalence of HIV infection among MSM who have high selfperceptions for HIV infection encouraged the desire to know the status of HIV (Torres et al, 2017) In a study in India, components of macroeconomic vulnerability showed that educational levels, employment status, HIV awareness, and the area in which they live have an impact on HIV transmission (Lall, 2014). The main factors of people to do VCT test to find out the status of HIV were due to the decreased of physical health, death of a sexual partner or child (Musheke et al, 2013).…”
Section: The Effect Of the Intention To Knowmentioning
confidence: 99%
“…This study was in accordance with a study done by Xu et al (2017), which stated that patients who want to know the status of HIV would be able to live their lives if they have family support and there was no discrimination. The prevalence of HIV infection among MSM who have high selfperceptions for HIV infection encouraged the desire to know the status of HIV (Torres et al, 2017) In a study in India, components of macroeconomic vulnerability showed that educational levels, employment status, HIV awareness, and the area in which they live have an impact on HIV transmission (Lall, 2014). The main factors of people to do VCT test to find out the status of HIV were due to the decreased of physical health, death of a sexual partner or child (Musheke et al, 2013).…”
Section: The Effect Of the Intention To Knowmentioning
confidence: 99%
“…This becomes crucial for India as it has an unmet need for family planning (FP) at 13% in the general population with a higher reported need of 17% in PLHIV group [ 11 , 12 ]. Further, women’s socioeconomic status could have an association with their sero-status, as HIV-positive women are significantly more likely to have low levels of education than their HIV-negative counterparts [ 13 ]. Association of socio-economic determinants like age, education, place of residence along with gender-based discrimination and domestic violence faced by Indian women make them vulnerable to both HIV and unintended pregnancies.…”
Section: Introductionmentioning
confidence: 99%